2014
DOI: 10.4161/19336896.2014.983745
|View full text |Cite
|
Sign up to set email alerts
|

A conservative mutant of a proteolytic fragment produced during fibril formation enhances fibrillogenesis

Abstract: The fibrillogenesis of a peptide corresponding to residues 35-51 of human α-lactalbumin (¹GYDTQAIVENNESTEYG¹⁷) can be dramatically enhanced by the addition of a tetrapeptide TDYG homologous to its C-terminus (TEYG). Generation of spontaneous hydrolytic products similar to this peptide was demonstrated by mass-spectrometry analysis of GYDTQAIVENNESTEYG peptide solution components during fibrillogenesis. Possible mechanisms and roles of short peptides in protein metabolism are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Fibrillogenesis of a peptide corresponding to residues 35–51 of human α-LA (1GYDTQAIVENNESTEYG17, WT peptide) at pH 2 can be dramatically enhanced by the addition of a tetrapeptide TDYG (R peptide) homologous to its C-terminus (TEYG) [ 139 ]. Computer simulations showed that WT peptide can form oligomeric β-like structures due to interactions of the tyrosine residues in the mirror symmetric tails (GYDT and TEYG) of the peptide molecules in antiparallel orientation.…”
Section: Fibrillation Of α-Lactalbumin; Nanoparticles and Nanotubementioning
confidence: 99%
See 2 more Smart Citations
“…Fibrillogenesis of a peptide corresponding to residues 35–51 of human α-LA (1GYDTQAIVENNESTEYG17, WT peptide) at pH 2 can be dramatically enhanced by the addition of a tetrapeptide TDYG (R peptide) homologous to its C-terminus (TEYG) [ 139 ]. Computer simulations showed that WT peptide can form oligomeric β-like structures due to interactions of the tyrosine residues in the mirror symmetric tails (GYDT and TEYG) of the peptide molecules in antiparallel orientation.…”
Section: Fibrillation Of α-Lactalbumin; Nanoparticles and Nanotubementioning
confidence: 99%
“…Computer simulations showed that WT peptide can form oligomeric β-like structures due to interactions of the tyrosine residues in the mirror symmetric tails (GYDT and TEYG) of the peptide molecules in antiparallel orientation. The authors suggested that peptide R could more rapidly interact with the 1GYDT4 part of WT, stabilizing it in conformation predisposed to oligomerization due to more rapid diffusion and lack of steric interference [ 139 ].…”
Section: Fibrillation Of α-Lactalbumin; Nanoparticles and Nanotubementioning
confidence: 99%
See 1 more Smart Citation
“…The induction of conformational transitions can also be caused by amyloidogenic protein fragments (Figures 4 and 5 ). This has been specifically shown for the Syrian hamster prion protein PrP [ 27 ] and alpha-lactalbumin [ 28 , 29 ]; it has also been shown that the NAGDVAFV peptide fibrils of lactoferrin are capable of inducing specific binding to the whole protein [ 30 ], while lysozyme fibrillogenesis is accelerated by the nicking or adding of fragments formed after its autohydrolysis by aspartate [ 31 ].…”
Section: Induction Of Conformational Transitionsmentioning
confidence: 99%
“…It is interesting to note that those peptides for the prion protein PrP [ 27 ], alpha-lactalbumin [ 28 , 29 ], and PB1 [ 32 ], all of which are capable of inducing a parent protein conformational transition, contain mirror-symmetrical motifs (MSMs) within their primary structures ( Figure 6 ) [ 34 ]. Mirror-symmetrical motif formation can arise due to amplification of repeats in DNA and have a role in the formation of the tertiary structure in proteins [ 35 ].…”
Section: Induction Of Conformational Transitionsmentioning
confidence: 99%